Primary care detection of Alzheimer's disease using a self-administered digital cognitive test and blood biomarkers - Tideman, Pontus; Karlsson, Linda ; 0000-0002-0630-772X; Strandberg, Olof; Calling, Susanna; Smith, Ruben; Midlöv, Patrik ; 0000-0002-5871-8731; Verghese, Philip B; Braunstein, Joel B; Mattsson-Carlgren, Niklas ; 0000-0002-8885-7724; Stomrud, Erik ; 0000-0002-0841-5580; Palmqvist, Sebastian ; 0000-0002-9267-1930; Hansson, Oskar ; 0000-0001-8467-7286 (Nature Medicine, 2025)
After the clinical implementation of amyloid-β-targeting therapies for people with cognitive impairment due to Alzheimer's disease (AD), there is an urgent need to efficiently identify this patient population in primary care. Therefore, we created a brief and self-administered digital cognitive test battery (BioCog). Based on its sub-scores, a logistic regression model was developed in a secondary care cohort (n = 223) and then evaluated in an independent primary care cohort comprising 19 primary care centers (n = 403). In primary care, BioCog had an accuracy of 85% when using a single cutoff to define cognitive impairment, which was significantly better than the assessment of primary care physicians (accuracy 73%). The accuracy increased to 90% when using a two-cutoff approach. BioCog had significantly higher accuracy than standard paper-and-pencil tests (that is, Mini-Mental State Examination, Montreal Cognitive Assessment, Mini-Cog) and another digital cognitive test. Furthermore, BioCog combined with a blood test could detect clinical, biomarker-verified AD with an accuracy of 90% (one cutoff), significantly better than standard-of-care (accuracy 70%) or when using the blood test alone (accuracy 80%). In conclusion, this proof-of-concept study shows that a brief, self-administered digital cognitive test battery can detect cognitive impairment and, when combined with a blood test, accurately identify clinical AD in primary care.
© 2025. The Author(s).